Effect and possible mechanism of monocyte-derived VEGF on monocyte–endothelial cellular adhesion after electrical burns. Issue 4 (June 2015) - Ruan, Qiongfang; Zhao, Chaoli; Ye, Ziqing; Ruan, Jingjing; Xie, Qionghui; Xie, Weiguo
Abstract Objective One of the major obstacles in the treatment of severe electrical burns is properly handling the resulting uncontrolled inflammation. Such inflammation often causes secondary injury and necrosis, thus complicating patient outcomes. Vascular endothelial grow factor (VEGF) has emerged as an important mediator for the recruitment of monocytes to the site inflammation. This study was designed to explore the effects and possible mechanism of VEGF on monocyte–endothelial cellular adhesion. To do so, we used a cultured human monocytic cell line (THP-1) that was stimulated with serum derived from rats that had received electrical burns. Methods Serum was obtained from rats that had received electrical burns. Both the VEGF and soluble flt-1 (sflt-1) concentrations of the serum were determined by double-antibody sandwich ELISA. The concentrations of VEGF, sflt-1, and TNF-α obtained from the cell-free cultured supernatant of THP-1 cells that had been exposed to the serum were then determined by double-antibody sandwich ELISA. Serum-stimulated THP-1 cells were added to wells with a monolayer of endothelial cells to detect the level of monocyte–endothelial cells adhesion. Finally, the state of phosphorylation of AKT was determined by Western blotting. Results Both in vivo and in vitro studies showed that compared to controls, the levels of VEGF were significantly increased after electrical burns. This increased was accompanied by a reduction of sflt-1 levels. Furthermore, the serum of rats that had received electrical burns was able to both activate monocytes to secrete TNF-α and enhance monocyte–endothelial cell adhesion. Treatment with the serum also resulted in an up-regulation of the phosphorylation of AKT, but had no effect on the total levels of AKT. Phosphatidylinositide 3-kinases (PI3K) inhibition decreased the number of THP-1 cells that were adhered to endothelial cells. Finally, sequestering VEGF with sflt-1 was able to reduce the effect on monocyte–endothelial cells adhesion by blocking the PI3K signaling pathway. Conclusion Our results indicate that VEGF is implicated in the pathogenesis of inflammation after electrical burns. Inhibition of VEGF activity could attenuate monocyte–endothelial cells adhesion by suppressing the state of phosphorylation of AKT, which is downstream of the PI3K signaling pathway.